Penerapan Algoritma C.45 Untuk Analisis Pengadaan Peralatan dan Mesin Kantor - Amalia Iftitah; Resad Setyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Badan Keuangan dan Aset Daerah (BKAD) of Banyumas Regency is an agency under the auspices of the regional central government of Banyumas Regency. BKAD Banyumas Regency has various types of Kartu Inventaris Barang(KIB) which are still not well managed, namely KIB office equipment and machines and make it difficult to procure office equipment, so a decision support system is needed to predict the proposed procurement of office equipment and machines. This prediction is made with the aim of facilitating the asset sub-sector in particular in carrying out the task. This prediction has benefits in implementing the replacement of office equipment and machines that can be managed properly according to employee needs so that employee performance is maximized. Methods of data collection using survey methods, literature, and interviews with members of the asset sub-sector. The data processing method in this report uses a quantitative method with the C.45 algorithm. An analysis of the prediction of proposing office equipment and machines using the C.45 algorithm with the help of the Rapidminer Application is able to provide results in the form of a decision tree that can be used by members of the asset sub-sector in making decisions. Based on the predicted results for proposing the procurement of office equipment, all equipment whose year of purchase/procurement was less than or equal to 1998, equipment in damaged condition with a year of purchase/procurement of more than 1998, equipment made of plastic/ebonite and plastic in poor condition with year of purchase/procurement more than 1998.